2005
DOI: 10.1098/rspb.2005.3373
|View full text |Cite
|
Sign up to set email alerts
|

Predation risk induces changes in nest-site selection and clutch size in the Siberian jay

Abstract: Life-history theory predicts that an individual should reduce its reproductive efforts by laying a smaller clutch size when high risk of nest predation reduces the value of current reproduction. Evidence in favour of this 'nest predation hypothesis', however, is scarce and based largely on correlative analyses. Here, we manipulated perceived risk of nest predation in the Siberian jay Perisoreus infaustus using playback involving a mixture of calls by corvid nest predators in the vicinity of nest sites. In resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
257
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 289 publications
(278 citation statements)
references
References 32 publications
(43 reference statements)
13
257
3
Order By: Relevance
“…Coastal territories experienced a much higher predation risk, and coastal females had a greater cumulative seasonal investment in eggs. This investment pattern follows a within-season, bethedging strategy-as expected under conditions defined by a high probability of failure (Eggers et al 2006;Slagsvold 1984). Coastal individuals also exhibited numerous behavioral adaptations to increased predation risk.…”
Section: Discussionmentioning
confidence: 60%
“…Coastal territories experienced a much higher predation risk, and coastal females had a greater cumulative seasonal investment in eggs. This investment pattern follows a within-season, bethedging strategy-as expected under conditions defined by a high probability of failure (Eggers et al 2006;Slagsvold 1984). Coastal individuals also exhibited numerous behavioral adaptations to increased predation risk.…”
Section: Discussionmentioning
confidence: 60%
“…Preference for tall nest trees is common among many forest-dwelling raptors (Titus and Mosher 1981;Bednarz and Dinsmore 1982) and may be the evolutionary result of several stimuli such as reduced thermoregulatory stress or predation risk. Martin (1993) and Eggers et al (2006) described how predation risks can influence nesting habitat selection of many bird species, and Franklin et al (2000) showed thermoregulatory considerations may influence habitat selection of northern spotted owls Strix occidentalis.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the risk of predation exerts strong selection pressures not only on the location and design of birds' nests but also on the behaviors of the parent birds when they visit the nest site (reviewed by Martin, 1993;Lima, 2009;Mainwaring et al, 2014bMainwaring et al, , 2015Ibáñez-Álamo et al, 2015). Accordingly, the risk of predation influences aspects of nest site selection (Marzluff, 1988;Forstmeier and Weiss, 2004;Eggers et al, 2006) and nest design (Biancucci and Martin, 2010;Lovell et al, 2013) in a wide range of birds. For example, the open cup nests of common blackbirds (Turdus merula) that were experimentally increased in size were predated more often than either control nests that remained unchanged in size or nests that were experimentally decreased in size (Møller, 1990a).…”
Section: Predator Avoidancementioning
confidence: 99%